Leadership in Action : Dispersed Teams Need to Get Off on the Right Foot - Sessa, Valerie; Hansen, Michael; Kossler, Michael; Prestridge, Sonya (Center for Creative Leadership, 2001)
The latest research by CCL sheds light on how members of dispersed teams interact, how to best build and support such teams, and how dispersed teams achieve their goals.